2011
DOI: 10.1097/mph.0b013e3181f6921a
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Life-threatening Infections in Children With Febrile Neutropenia

Abstract: Evaluation of important RFs and judging the severity of patients' condition by studying the importance and relationship between RF at the time of admission can be a useful method for screening LTI in children with FN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Apart from younger age, bivariate analysis identified an association of mucositis with FN and MDI: Higher grades of mucositis correlated with more FN episodes and higher infection rates. These findings are in concordance with the results of other studies that found associations of mucositis with FN [8,38] and severe infections [39] in bivariate analysis. Indeed, mucositis is the result of a complex series of biological events involving inflammation, alteration of the local tissue response, apoptosis of the basal cell layer and loss of mucosal integrity that facilitates migration of mucosal microorganisms and makes the individual prone to invasive bacterial, fungal and viral infection [40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 93%
“…Apart from younger age, bivariate analysis identified an association of mucositis with FN and MDI: Higher grades of mucositis correlated with more FN episodes and higher infection rates. These findings are in concordance with the results of other studies that found associations of mucositis with FN [8,38] and severe infections [39] in bivariate analysis. Indeed, mucositis is the result of a complex series of biological events involving inflammation, alteration of the local tissue response, apoptosis of the basal cell layer and loss of mucosal integrity that facilitates migration of mucosal microorganisms and makes the individual prone to invasive bacterial, fungal and viral infection [40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 93%
“…Four studies examined rules to predict significant medical complications; a group of outcomes generally encompassing death, intensive care admission, significant bacterial or fungal infection, and need for organ support such as supplemental oxygen, inotropes or dialysis [7], [14], [16], [17]. Two examined rules to predict bacteraemia [16], [18], and one intensive care admission [15].…”
Section: Resultsmentioning
confidence: 99%
“…Besides the 5 clinical decision rules (CDR) mentioned above [2][4],[6],[7], only 3 of 13 further recently reviewed [5],[20] studies generating CDRs for pediatric FN reported non-significant univariate associations of hemoglobin with different AE [21][23]. Since hemoglobin is routinely assessed at presentation with FN, this may well represent underreporting of negative results.…”
Section: Discussionmentioning
confidence: 99%